2002
DOI: 10.1002/jnr.10416
|View full text |Cite
|
Sign up to set email alerts
|

Multiple aspects of homocysteine neurotoxicity: Glutamate excitotoxicity, kinase hyperactivation and DNA damage

Abstract: Homocysteine (HC) is a neurotoxic amino acid that accumulates in several neurological disorders including Alzheimer's disease (AD). We examined the consequences of treatment of cultured murine cortical neurons with HC. Homocysteine-induced increases in cytosolic calcium, reactive oxygen species, phospho-tau immunoreactivity and externalized phosphatidyl serine (indicative of apoptosis). Homocysteine-induced calcium influx through NMDA channel activation, which stimulated glutamate excitotoxicity, as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
218
2
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(235 citation statements)
references
References 49 publications
10
218
2
5
Order By: Relevance
“…The functional implications of changes in tau phosphorylation are numerous, because epitope-specific phosphorylation differentially modulates the distribution, degradation, aggregation, binding to microtubules and other proteins such as PP2A, and microtubuleregulatory functions of tau (Brandt et al, 2005;Stoothoff and Johnson, 2005). It has been reported that exogenous Hcy and folate deficiency in cultured neurons can increase SAH and/or decrease SAM levels and promote tau phosphorylation (Ho et al, 2002(Ho et al, , 2003. Our studies show that some of these effects are directly mediated by PP2A.…”
Section: Discussionmentioning
confidence: 55%
“…The functional implications of changes in tau phosphorylation are numerous, because epitope-specific phosphorylation differentially modulates the distribution, degradation, aggregation, binding to microtubules and other proteins such as PP2A, and microtubuleregulatory functions of tau (Brandt et al, 2005;Stoothoff and Johnson, 2005). It has been reported that exogenous Hcy and folate deficiency in cultured neurons can increase SAH and/or decrease SAM levels and promote tau phosphorylation (Ho et al, 2002(Ho et al, , 2003. Our studies show that some of these effects are directly mediated by PP2A.…”
Section: Discussionmentioning
confidence: 55%
“…Other investigations also support the finding of elevated homocysteine levels in MS patients compared with healthy controls [20], [21] and [22]. It is hypothesized that the nervous system may be particularly sensitive to pHcy as it promotes excitotoxicity by stimulation of NMDA receptors and damages neuronal DNA hence triggering apoptosis in neuronal cells [14] and [23]. Ergo, although our findings suggest no association between MTHFR A1298C and MTRR A66G and MS, other variants associated with the homocysteine metabolism cascade may still contribute to MS susceptibility.…”
Section: Discussionmentioning
confidence: 63%
“…51,52 Extra-cellular homocysteine has been found to be toxic to cultured neurons and neuron cells via stimulation of NMDA receptors, enhancing oxidative stress and inducing DNA damage eventually resulting in apoptosis and adverse effects on synaptic and glial function. 51,53,54 Recently, experiments with mice have shown that these mechanisms are not only important in cultured embryonic premitotic neurons, but in the adult postmitotic neurons as well. 55 The deleterious effect of MTHFR dysfunction on brain development was observed in individuals with a severe deficiency of this enzyme, resulting in delayed psychomotor development, mental retardation and psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%